(untitled) (River Edge, N.J., 2002)
Papers presented at the conference held in Cortona, Italy, June 25-29, 2001. Deals mainly with mathematical techniques for the investigation of physical systems.
Keywords: Smart materials,Vật liệu thông minh; Mathematical models,Mô hình toán